Exploring the risk association between psoriasis and chronic obstructive pulmonary disease, and asthma using the NHIS database - Mingyu Liu; Shuming Ji; Pengxin Ye; Min Gong; Qilin Liu (PLoS ONE, 2026)
Background Asthma (AS) and chronic obstructive pulmonary disease (COPD) are prevalent chronic airway disorders with shared inflammatory pathways. Considering the systemic inflammatory nature of psoriasis, this study utilized the National Health Interview Survey (NHIS) to investigate its potential association with COPD and AS. Methods Data from the 2023 NHIS were analyzed, with participants selected based on specific inclusion criteria. A baseline table was constructed, and multivariate logistic regression models, along with risk stratification analysis, were employed to examine the correlations between psoriasis and COPD and AS. Receiver operating characteristic (ROC) analysis was conducted to assess the predictive value for both conditions. Results A total of 27,106 participants were included in the study. Significant differences were observed in the baseline characteristics of psoriasis, age, race, region, gender, education, marital status, employment, income, smoking habits, health status, mental health, disability, heart attack history, BMI, prediabetes, cancer, hypertension, hypercholesterolemia, arthritis, coronary heart disease, stroke, health insurance, anxiety, and depression ( P < 0.001). Multivariate logistic regression revealed a strong association between psoriasis and COPD (model 1: OR 2.63, 95% CI: 2.13–3.23, P < 0.001; model 2: OR 2.43, 95% CI: 1.95–2.99, P < 0.001; model 3: OR 1.54, 95% CI: 1.21–1.96, P < 0.001). A similar association was found between psoriasis and AS (model 1: OR 1.68, 95% CI: 1.42–1.97, P < 0.001; model 2: OR 1.74, 95% CI: 1.47–2.05, P < 0.001; model 3: OR 1.32, 95% CI: 1.11–1.56, P < 0.01). The ROC analysis based on model 3 demonstrated substantial predictive power of psoriasis for COPD, with an AUC of 0.881. Conclusion Psoriasis was identified to have a strong association with COPD and AS, which provided valuable insights into understanding the pathogenesis of these diseases.